PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI (Studi Kasus pada PT Bank BRI KC Sukoharjo) - nugraha, ardian (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
This research is conducted in order to find out the significance of the influence of (1) organizational culture, (2) employee performance and (3) work motivation as mediation at PT Bank BRI KC Sukoharjo Sampling using census techniques. Data collection techniques using a questionnaire through the test of validity and reliability. Analysis techniques through multiple linear regression, t test, F test, R2 test and the classic assumption test. From the results of the validity test, the research instrument is valid. The reliability test results are reliable. From the classic assumption test, the multicollinearity test passed the test, the heteroscedasticity test passed the test, the autocorrelation test passed the test and the normality test passed the test. The analysis shows that organizational culture has a significant effect on employee performance with work motivation as a mediator.Â Keywords: organizational culture, employee performance motivation